Long-Term Stability of Novel Crucible Systems for the Growth of Oxygen-Free Czochralski Silicon Crystals - Sturm, Felix; Trempa, Matthias; Schuster, Gordian; Hegermann, Rainer; Goetz, Philipp; Wagner, Rolf; Barroso, Gilvan; Meisner, Patrick; Reimann, Christian; Friedrich, Jochen (Crystals, 2023)
The replacement of the silica glass crucible by oxygen-free crucible materials in silicon Czochralski (Cz) growth technology could be a key factor to obtaining Cz silicon, with extremely low oxygen contamination < 1 x 10(17) at/cm(3) required for power electronic applications. So far, isostatic pressed graphite or nitrogen-bonded silicon nitride (NSN) crucible material, in combination with a chemical vapor deposited silicon nitride (CVD-Si3N4) surface coating, could be identified as promising materials by first short-term experiments. However, for the evaluation of their potential for industrial scale Cz growth application, the knowledge about the long-term behavior of these crucible setups is mandatory. For that purpose, the different materials were brought in contact with silicon melt up to 60 h to investigate the infiltration and dissolution behavior. The chosen graphite, as well as the pore-sealed NSN material, revealed a subordinated infiltration-depth of <= 1 mm and dissolution of <= 275 mu m by the silicon melt, so they basically fulfilled the general safety requirements for Cz application. Further, the highly pure and dense CVD Si3N4 crucible coating showed no measurable infiltration as well as minor dissolution of <= 50 mu m and may further acts as a nucleation site for nitrogen-based precipitates. Consequently, these novel crucible systems have a high potential to withstand the stresses during industrial Cz growth considering that more research on the process side relating to the particle transport in the silicon melt is needed.
CRIS-Team WoS Importer:2023-02-10